SMART CLASSROOMS AND E-LEARNING: THE FUTURE OF BUSINESS EDUCATION - Inamdar, Varada; Jadhav, Priyanka; Singh, Shweta (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The fast-paced evolution of smart classrooms and e-learning technologies is revolutionizing business education by improving student engagement, retention of knowledge, and employability. This research investigates the effects of technology-enriched learning environments on business education, juxtaposing conventional classroom environments with smart classrooms and e-learning platforms. The study uses a quantitative methodology based on a structured questionnaire and gathers responses from 400 students of business education in Pune. Analysis of data is carried out utilizing Regression Analysis and ANOVA on SPSS to check for the hypotheses. Findings show that e-learning and smart classrooms have greatly enhanced student knowledge retention, and the level of participation compared to non-smart classes. Regression analyses show a robust positive relationship between smart classrooms and increased employability, while ANOVA reiterates there is a significant statistical difference between engagement and learning in smart environments and non-smart environments. Demographic studies show that the majority of respondents are young undergraduates pursuing full-time programs. The research concludes that technology-enabled education has a positive impact on business education through an interactive, adaptive, and flexible learning experience. The challenges that need solutions include faculty acclimatization, digital literacy, and ethics. Based on the findings, the recommendation is for investment in faculty work, embedding AI-enabled analytics to allow personal learning, and making it inclusive by building up infrastructure. Thus, these findings have practical implications for business educators, policymakers, and institutions so as to better engage the use of smart classrooms and e-learning to strengthen effective and sustainable business education